ANALISIS IMPLEMENTASI STANDAR AKUNTANSI KEUANGAN ENTITAS MIKRO KECIL DAN MENENGAH (SAK EMKM) PADA PENYUSUNAN LAPORAN KEUANGAN UMKM (STUDI PADA CAFE D’QAISAR) - Abdul Manaf; Elyanti Rosmanidar; Marissa Putriana (Nusantara Hasana Journal, 2026)
This Study Aims To Analyze The Implementation Of Financial Accounting Standards For Micro, Small, And Medium Entities (SAK EMKM) In The Preparation Of Financial Statements At Cafe D’qaisar, Jambi City. This Research Uses A Descriptive Qualitative Method With A Case Study Approach. Data Were Collected Through Interviews, Observations, And Documentation. The Analysis Employed The Dean J. Champion Formula To Measure The Level Of Compliance.The Results Show That The Implementation Of Sak Emkm At Cafe D’qaisar Has Not Been Fully Carried Out. The Measurement Aspect Reached 100% Compliance, And The Recognition Aspect Reached 80%. However, The Presentation Aspect Only Reached 40% Due To The Absence Of Depreciation Expense Recognition And The Lack Of Notes To Financial Statements (Calk). The Main Obstacles Include Limited Accounting Knowledge Of The Owner, Focus On Daily Operational Activities, And The Perception That Accounting Standards Are Complex.Therefore, This Study Suggests The Use Of Digital Accounting Applications To Improve Financial Reporting Quality In Accordance With SAK EMKM.